2017
DOI: 10.1007/s40279-017-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-Muscular Structures Can Limit the Maximal Joint Range of Motion during Stretching

Abstract: Stretching is widely used in sport training and clinical practice with the aim of increasing muscle-tendon extensibility and joint range of motion. The underlying assumption is that extensibility increases as a result of increased passive tension applied to muscle-tendon units. In some stretching protocols, this condition is not always met sufficiently to trigger adaptation within the muscle-tendon unit. For example, there is experimental evidence that both acute and chronic stretching interventions may increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…Thus, it remains unclear whether the current findings hold true for females. On the other hand, the elasticity of non-muscular tissues such as nerve and fascia has recently been proposed to influence joint flexibility [33,34]. Further researches are required to examine these points.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it remains unclear whether the current findings hold true for females. On the other hand, the elasticity of non-muscular tissues such as nerve and fascia has recently been proposed to influence joint flexibility [33,34]. Further researches are required to examine these points.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the involvement of other muscles such as the mono-articular gluteus maximus should be negligible. Another possible reason is the variation in the pelvic position [22,23] and stiffness of non-muscular tissue such as nerve, fascia, and tendon [27]. Further studies are warranted to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…This change occurred in the absence of any changes in the gastrocnemius medialis (GM) local stiffness and ankle torque 8 . Because there is no muscle-tendon unit crossing both the hip and ankle joints, these results have suggested that non-muscular structures may play a role in the limitation of maximal ankle ROM in dorsiflexion 9 . A possible candidate to explain this effect is the sciatic nerve that extends from the spine through branches to the foot, and like most other connective tissues, exhibits visco-elastic behavior 10 , 11 .…”
Section: Introductionmentioning
confidence: 96%